2017
DOI: 10.1371/journal.pone.0187327
|View full text |Cite
|
Sign up to set email alerts
|

Early structural changes of the heart after experimental polytrauma and hemorrhagic shock

Abstract: Evidence is emerging that systemic inflammation after trauma drives structural and functional impairment of cardiomyocytes and leads to cardiac dysfunction, thus worsening the outcome of polytrauma patients. This study investigates the structural and molecular changes in heart tissue 4 h after multiple injuries with additional hemorrhagic shock using a clinically relevant rodent model of polytrauma. We determined mediators of systemic inflammation (keratinocyte chemoattractant, macrophage chemotactic protein 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
(31 reference statements)
2
31
0
Order By: Relevance
“…The gap junction protein Cx43 was translocated from intercalated discs into the cytoplasm of the cardiomyocytes after multiple trauma in both parts of the left ventricle. This translocation of Cx43 was already demonstrated by our group in earlier studies after multiple trauma in pigs and mice [6,27], after blunt chest trauma in rats [16], after new-born asphyxia in pigs [28] and during chronic psychosocial stress in mice [29]. The endocytosis of Cx43 has been linked to alterations in the electromechanical communication of CMs and is therefore associated with are represented as white bars, 4 h after trauma as medium grey bars and 6 h after trauma as dark grey bars.…”
Section: Discussionsupporting
confidence: 72%
“…The gap junction protein Cx43 was translocated from intercalated discs into the cytoplasm of the cardiomyocytes after multiple trauma in both parts of the left ventricle. This translocation of Cx43 was already demonstrated by our group in earlier studies after multiple trauma in pigs and mice [6,27], after blunt chest trauma in rats [16], after new-born asphyxia in pigs [28] and during chronic psychosocial stress in mice [29]. The endocytosis of Cx43 has been linked to alterations in the electromechanical communication of CMs and is therefore associated with are represented as white bars, 4 h after trauma as medium grey bars and 6 h after trauma as dark grey bars.…”
Section: Discussionsupporting
confidence: 72%
“…While Weckbach et al . compared their experimental PT model consisting of a blunt chest trauma, head injury, femur fracture and soft tissue injury with different two-hit trauma models, and on the one hand has demonstrated that injury pattern does matter 23 , importantly, others underlined the not deniable relevance of HS after experimental PT on the other hand 24,25,42,43 . End organ damage in both murine PT and HS model demonstrate elevated transaminases after two or 24 h 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In traumatized patients, enhanced levels of circulating histones were correlated with the Sequential Organ Failure Assessment score, endothelial damage and the activation of the coagulation system [8]. In experimental blunt chest trauma in rats and in experimental multiple trauma in pigs and mice, we observed a systemic release of extracellular histones [3][4][5].…”
Section: Introductionmentioning
confidence: 79%
“…Post-traumatic cardiac injury can be caused by mechanical forces on the heart, particularly in the case of blunt chest trauma [3][4][5] or by inflammation, which mediates secondary cardiac damage. Severe trauma often leads to a systemic inflammatory response, accompanied by the release of danger associated molecular patterns (DAMPs), such as the high mobility group box-1 protein (HMGB-1) and extracellular histones.…”
Section: Introductionmentioning
confidence: 99%